Amino Acids and IGF1 Regulation of Fish Muscle Growth Revealed by Transcriptome and microRNAome Integrative Analyses of Pacu (Piaractus mesopotamicus) Myotubes - Duran, Bruno Oliveira Silva; Zanella, Bruna Tereza Thomazini [UNESP]; Perez, Erika Stefani [UNESP]; Mareco, Edson Assunção; Blasco, Josefina; Dal‐pai‐silva, Maeli [UNESP]; de la serrana, Daniel Garcia (MDPI, 2022)
Amino acids (AA) and IGF1 have been demonstrated to play essential roles in protein synthesis and fish muscle growth. The myoblast cell culture is useful for studying muscle regula-tion, and omics data have contributed enormously to understanding its molecular biology. How-ever, to our knowledge, no study has performed the large‐scale sequencing of fish‐cultured muscle cells stimulated with pro‐growth signals. In this work, we obtained the transcriptome and mi-croRNAome of pacu (Piaractus mesopotamicus)‐cultured myotubes treated with AA or IGF1. We identified 1228 and 534 genes differentially expressed by AA and IGF1. An enrichment analysis showed that AA treatment induced chromosomal changes, mitosis, and muscle differentiation, while IGF1 modulated IGF/PI3K signaling, metabolic alteration, and matrix structure. In addition, potential molecular markers were similarly modulated by both treatments. Muscle‐miRNAs (miR‐1, ‐133, ‐206 and ‐499) were up‐regulated, especially in AA samples, and we identified molecular networks with omics integration. Two pairs of genes and miRNAs demonstrated a high‐level relationship, and involvement in myogenesis and muscle growth: marcksb and miR‐29b in AA, and mmp14b and miR‐338‐5p in IGF1. Our work helps to elucidate fish muscle physiology and metabolism, highlights potential molecular markers, and creates a perspective for improve-ments in aquaculture and in in vitro meat production.
Keywords: Amino acids; Cell culture; IGF1; Muscle growth; Omics